Interactive communication and academic achievement as indicators of the quality of the e-learning program - Saleh, Shoeb; Ibrahim, Khaled Ahmed Abdel-Al (Research Journal in Advanced Humanities, 2025)
Considering the worldwide digital transformation witnessed by the education sector, especially after the consequences of the Covid-19 pandemic, this study aimed to investigate the effectiveness of an e-learning program based on the Moodle platform in developing interactive communication and increasing the level of academic achievement, as these two variables are key indicators of the quality of e-educational programs. The program was administrated to a sample of students of the Methods of Teaching Legality Sciences course, where a quasi-experimental methodology was followed that compares an experimental group that received education through the electronic program, and a control group followed the traditional method of learning. The results of this study showed the effectiveness of the suggested electronic program, based on the Moodle system, in developing interactive communication in e-learning and increasing the level of academic achievement among students.One of the main achievements provided by this study is to emphasize that electronic interaction does not have an extra value, but it is an essential element of high-quality educational design, experimental data have proven that programs that were characterized by a high degree of interaction (whether the learner's interaction with the teacher, his colleagues or the content) clearly contributed to improving academic learning outcomes, and enhancing the sense of belonging and presence within the learning environment.This study provides a practical framework for measuring the effectiveness of electronic programs by tracking the dynamics of interaction within the Learning environment, analyzing the relationship between communication patterns (student-teacher, student-content, student-student) and actual educational outcomes. It also contributes to suggesting an evaluative model based on evidence-based educational practices, which can be adopted by higher education institutions to ensure the quality of design and implementation of their electronic courses.